Shadi Park Renovation with Social Development Emphasis: A Case Study Halabja City, Iraq - Mustafa, Mihraban Othman; Faraji, Masoumeh; Salih, Zaniar Jamal; Rasheed, Muhammed Saeed (Kurdistan Journal of Applied Research, 2021)
The expansion of urbanization and the lack of open spaces in cities, urban green spaces have become very important, especially in recent decades. Among urban green spaces, parks are important because they have leisure and recreational functions, and the favorable physical and mental effects on humans have been proven today. Depreciation of materials, park equipment, destruction of vegetation and lifestyle changes over time have changed the needs and desires of the people and caused the old parks do not meet the needs of citizens. Today, improving parks is a new approach that makes parks matches the demands human beings have evolved over time with the advancement of technology. Shadi Park in Iraq is one of the regional urban parks; the lack of its design, as well as the wear and tear of some uses, lack of optimal lighting system and various uses by different age groups reduces the number of visits. In this research, based on field perceptions of the park and public opinion polls, prioritization and solutions to strengthen the presence of people has been pointed out. The results of the questionnaire indicate the priority of people’s demands, the most important of which include: building a sports venue for women, proper service of restaurants and cafes during the day and night, the presence of swimming pools and fountains in the park, parking at the entrances, space allocation to hold cultural and artistic festivals.